Impact of Rukiga Proverbs on the Girl Child Education: A Case Study of Kinkizi High School in Kanungu Town Council Kanungu District. - Amanya, Ritah (Kabale University, 2024)
The study investigated the impact of Rukiga proverbs on girl child education at Kinkizi High School in Kanungu District, with objectives to identify the causes of gender discrimination in Rukiga proverbs, examine the characteristics of proverbs used by secondary school students, and analyze manifestations of gender-based discrimination. Using a descriptive research design and a sample of 40 respondents through questionnaires and interviews, findings revealed that gender discrimination in proverbs stems from social division of labor, social status, and cultural practices that perpetuate male dominance. Features of proverbs commonly used by students included simplicity, straightforwardness, and the ability to convey lessons, while manifestations of discrimination were evident in proverbs such as "a man of straw is worth a woman of gold" and "a woman and a glass are ever in danger," which reinforce stereotypes about women's inferiority. The study concluded that Rukiga proverbs contribute significantly to the perpetuation of gender bias, which negatively affects the girl child’s education by embedding discriminatory attitudes in language and cultural practices. Recommendations included rejecting discriminatory proverbs like "women are wavering as the wind," valuing women’s advice as equally valid and insightful, and encouraging people to marry based on personal compatibility rather than academic qualifications, recognizing that family development relies on mutual respect and collaboration.